Systematic Analysis of User Perception for Interface Design Enhancement - Duan, Shiyu (Journal of Computer Science and Software Applications, 2025)
In view of the importance of user perception in the design of human-computer interaction interfaces, this study proposed a systematic evaluation index system. With functional perception, interactive perception, and emotional perception as the core, a multi-dimensional evaluation framework covering efficiency, feedback timeliness, information clarity, emotional pleasure, and aesthetic satisfaction was constructed. Through questionnaire surveys and the collection of user behavior data, the advantages and disadvantages of interface design were deeply analyzed. The results show that users have a high evaluation of information clarity and feedback timeliness, indicating that the interface performs well in logical design and operational response; while there is room for improvement in aesthetic satisfaction and emotional experience. Based on these findings, the study proposed targeted optimization strategies, which provided theoretical support and practical guidance for the design and improvement of interactive interfaces. In the future, the study will further expand the application scenarios of the perception evaluation model and explore more refined user experience optimization methods in combination with personalized technology. This study not only provides quantitative tools for the evaluation and optimization of human-computer interaction interfaces but also opens up new directions for user experience research.